2018
DOI: 10.1007/s11096-018-0608-x
|View full text |Cite
|
Sign up to set email alerts
|

Complementary medicines in pregnancy: recommendations and information sources of healthcare professionals in Australia

Abstract: Background The use of oral complementary and alternative medicines, including herbal supplements, has been increasing in pregnant women worldwide despite limited safety data. The decision of healthcare professionals to recommend these products to pregnant patients is controversial and not well documented. Objective To explore the recommendations and information sources that healthcare professionals use to determine the safety of oral non-prescribed supplements during pregnancy. Setting An Australian metropolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Moreover, until now, most probiotics have been registered as food supplements, not as medication; therefore, they did not have to fulfill the legal and/or efficacy criteria. Recently, Gilmartin, Vo-Tran, and Leung (2018) concluded that the available safety data of probiotics can be considered neither alarming nor having the robustness to suggest an absolute recommendation as safe during pregnancy. Safety depends on the strains within the products used, usually being one or more varieties of bifidobacterium, lactobacillus, saccharomyces , and streptococcus thermophiles .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, until now, most probiotics have been registered as food supplements, not as medication; therefore, they did not have to fulfill the legal and/or efficacy criteria. Recently, Gilmartin, Vo-Tran, and Leung (2018) concluded that the available safety data of probiotics can be considered neither alarming nor having the robustness to suggest an absolute recommendation as safe during pregnancy. Safety depends on the strains within the products used, usually being one or more varieties of bifidobacterium, lactobacillus, saccharomyces , and streptococcus thermophiles .…”
Section: Discussionmentioning
confidence: 99%
“…Safety depends on the strains within the products used, usually being one or more varieties of bifidobacterium, lactobacillus, saccharomyces , and streptococcus thermophiles . Especially for the latter two strains, no safety evidence is available (Gilmartin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary medicine use in pregnancy is well documented in the literature (although pregnancy safety data are extremely limited) with perceived benefits cited by women including ‘natural products’, self‐determination and belief in a holistic approach . Not surprisingly Australian health professionals are uncertain about the safety of complementary medicines in pregnancy and how to source or provide appropriate information …”
Section: Discussionmentioning
confidence: 99%
“…The scholarly literature reported that the rate of constipation during pregnancy ranged from about 11% to 38% (28). However, there are many studies proving that probiotics prevent constipation, a problem frequently encountered during pregnancy (29)(30)(31) Looking at the "Factors Affecting Women's Consumption of Probiotic Foods", the influence of health personnel on consumption of probiotics was minor (9.8%) ( Table 2). The study by Zeren (2015) emphasized that advertisements were the most influential factor that affect adults' consumption of probiotics (17).…”
Section: Discussionmentioning
confidence: 99%